STRATEGI KEPEMIMPINAN UNTUK MEWUJUDKAN MADRASAH YANG UNGGUL DAN ISLAMI DI MI NURUL ISLAM WONOGIRI - Novitasari, Giyarmi (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
The purpose of this study was to determine the leadership model implemented by the principal of MI Nurul Islam Wonogiri, the strategies implemented by the principal of MI Nurul Islam Wonogiri, and the results achieved from the leadership model of the principal of MI Nurul Islam Wonogiri. The type of research used was field research. The research method was descriptive qualitative. Data collection techniques were through observation, interviews, and documentation. The results of the study were: 1). The leadership model of the principal of MI Nurul Islam Wonogiri in realizing an excellent and Islamic school has a very important role because the principal serves as a manager, leader, supervisor, educator, administrator, innovator, motivator and determinant when making decisions or policies in the madrasah. 2). The strategy implemented by the principal of the madrasah towards realizing an excellent and Islamic school at MI Nurul Islam Wonogiri is by analyzing the needs of the madrasah community, creating a vision and mission, determining the goals and objectives of the madrasah, compiling programs, implementing programs that have been prepared and evaluating. 3). The results achieved from the model are: most of the graduates can continue to junior high schools, both public and private, can compete in competitions at both regional and national levels. Meanwhile, other achievements are that the quality and professionalism of teachers will increase, teachers will be more orderly in administration, more trained and creative in educating their students.